RELATIONSHIP BETWEEN HIGH-TEMPERATURE STRESS AND KEY PHYSIO-CHEMICAL, REACTIVE OXYGEN SPECIES AND ANTIOXIDANTS IN SPRING MAIZE HYBRIDS UNDER SEMI-ARID CONDITIONS - GHANI, A; YOUSAF, MI; HUSSAIN, K; HUSSAIN, S; RAZAQ, A; AKHTAR, N; IBRAR, I; KAMAL, N; ALI, B; KHAN, AM; SHAH, SWH; KHANUM, S; et al. (Biological and Clinical Sciences Research Journal, 2023)
High-temperature stress is one of the hurdles to achieving self-sufficiency and sustainability in maize production globally. The current experimental study was executed to identify the best suitable maize hybrids for heat-prone areas based on their performance. During spring 2020 & 2021, hybrids were sown under two stress conditions (a) control sowing and (b) late sowing. Kernel yield and related characteristics varied significantly among maize hybrids across both situations (P<0.05). Under High-temperature stress, correlation analysis uncovered a positive relationship between kernel yield and chlorophyll a (r = 0.77**, 0.54**), chlorophyll b (r = 0.72**, 0.66**), net photosynthetic rate (r = 0.71**, 0.67**), proline contents (r = 0.59*, 0.54**), hydrogen peroxide (r = 0.54*, 0.17NS), thousand kernel weight (r = 0.71*, 0.38*). Principal component and biplots analysis unveiled that the first four principal components accountable for 78.0% of the total variability among hybrids, with days to 50% silking, plant height, number of kernels per ear, kernel yield, net photosynthetic rate, hydrogen peroxide, malondialdehyde, and catalase as the primary sources of variation. Agglomerative Hierarchical Clustering (AHC) categorizes indigenous and multinational maize hybrids into three classes under stress treatments. The cluster analysis further revealed that indigenous hybrids, particularly YH-5395, YH-5482 and YH-5427 were the most heat tolerant and productive hybrids while YH-5404, P-1543 and JPL-1908 were among the most heat susceptible ones. Consequently, these hybrids are recommended for widespread cultivation, particularly in regions prone to high temperatures.